Tinjauan Yuridis terhadap Peran Media Sosial dalam Membentuk Pola Pikir Anak - Adelia Adelia (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study is motivated by the rapid development of social media, which has become an inseparable part of children’s lives in the digital era. While children gain educational and creative benefits from social media, they are also exposed to risks from negative content such as violence, pornography, and consumerist behavior, as reported by KPAI (2023) and data from We Are Social & Hootsuite (2024). To analyze this phenomenon, a library research method with a qualitative approach related to the development of children’s thinking patterns, and child protection regulations, aiming to gain a comprehensive understanding of social and juridical implications. The results indicate that social media plays a dual role in shaping children’s thinking: providing positive impacts through learning and creativity, while also posing potential negative influences if not properly supervised. Therefore, synergy is required between law enforcement based on Law Child Protection and Law Information and Electronic Transactions, parental supervision, and adequate digital literacy, so that social media can be used as an educational and safe tool for healthy child development.